PENGARUH TAMBAHAN PENGHASILAN PEGAWAI (TPP) TERHADAP PRODUKTIVITAS KERJA PEGAWAI DI SEKRETARIAT DAERAH KABUPATEN PASAMAN - Datamora, Sandro (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2022)
This research is associative quantitative, because a quantitative approach is used to explain phenomena. This research was conducted at the Regional Secretariat of Pasaman Regency. The sampling technique used in this study was total sampling. The total number ofp opulations in this study was all employees in the Regional Secretariat of Pasaman Regency, totaling 117 people. The results showed that there was an effect of providing additional employee income on the work productivity of employees at the Regional Secretariat of Pasaman Regency, that the value of the significance of the additional employee income variable on work productivity was 0.000 < 0.05. So that the better the provision of additional employee income, the more employee work productivity will increase.